INTERTEXTUALITY AND MEMORY IN EARLY CHINESE WRITINGS: A CASE STUDY FROM HUAINANZI. (September 2019) - Weingarten, Oliver
Abstract: This article aims to illustrate the usefulness of analytical approaches to early Chinese writings which center on effects of textual memory. Due to a dearth of contemporaneous descriptions, concrete practices of oral transmission, dictation, performance, and interpretation in Early China largely lie beyond the ken of present-day scholarship. But recurrence of linguistic-stylistic elements testifies to the presence of these elements in an author's memory. Memory should thus, in principle, provide a comparatively accessible perspective on textual production. To demonstrate this point, the article investigates verbal parallels to a passage from Huainanzi 淮南子 15, "Bing lüe" 兵略 (An Overview of the Military). The internal and distributional patterns as well as the qualitative properties of textual overlaps with other extant writings suggest a composition process that involved a particular type of textual memory. Parallels are fuzzy and patchy; they rarely exceed one or two clauses; they display an irregular distribution across intertexts; the similarities between them cut across linguistic and stylistic categories and recombine in unpredictable constellations. This bundle of characteristics suggests not so much systematic exploitation of trained mnemonic capacities to reproduce long stretches of text verbatim, but instead, a reliance on the aptness of linguistic-stylistic elements of various kinds to spring to mind piecemeal in particular thematic contexts. These specificities are captured well by Boris Gasparov's notion of "communicative fragments." To invoke an Aristotelian distinction, the resulting effects are close to those of unsupervised remembering rather than the deliberate, goal-directed cognitive activity of recollecting. Looking beyond the present study, it is hoped that future investigations of intertextuality will combine aspects of close reading—as in this article—and methods of digitally enhanced distant reading. This will likely help to elucidate distinct habits of text production and to devise more refined textual typologies, which might eventually feed into more nuanced literary, historical, and philosophical interpretations. 提要: 近幾十年來陸續有出土文獻面世，引起中西學者對抄本文化的研究熱誠。而受到抄本文化研究的啟發，西方漢學界近年特別關注於文本的撰述、傳授等相關議題。但古代的傳授方法與慣例，無論是口述、朗讀、聽寫等，其詳情現今恐無法而知。然而，各種互文現象則不然。重出的文字或語言模式屢屢載於諸文本上，可以證實這些元素必定原本存在作者的記憶中。 因此，本文主張，文本記憶的概念能為文本分析帶來一個有用的比較視角。本文以《淮南子・兵略》為例，藉其豐富的互文現象探討文本生產的問題。本文認為，《兵略》篇與其他著作相似甚至重複的言語既簡短且模糊，並非有意引用典故或固有語言資料。它們分散而不集中，難以確認文本間的影響；它們之間的相似性跨越了語言與形式的範疇，並以一種不可預期的方式重新組合；互文有令人印象深刻的形式或意涵，故易於回想；互文現象體現在特殊的語境中，大概是應其語境而發的。在《淮南子・兵略》中互文現象的這些特色令人想到 Boris Gasparov 所謂的溝通片斷（ communicative fragments），即常態性地出現在相似語境當中的語句或模式。本文認為，溝通片斷並非作者有意為之，而是意義或文理上固有聯繫而在創作過程中無意間提升到作者意識層次。而《兵略》篇則似乎為組合多種溝通片斷而成的，顯現出一種特定文本構成方法，亦即是作者有意無意中組合與語境相符的溝通片斷以撰文。